2009
DOI: 10.1016/j.visres.2009.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Cue contrast modulates the effects of exogenous attention on appearance

Abstract: Exogenous spatial attention can be automatically engaged by a cue presented in the visual periphery. To investigate the effects of exogenous attention, previous studies have generally used highly salient cues that reliably trigger attention. However, the cueing threshold of exogenous attention has been unexamined. We investigated whether the attentional effect varies with cue salience. We examined the magnitude of the attentional effect on apparent contrast [Carrasco, M., Ling, S., & Read, S. (2004). Attention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(77 citation statements)
references
References 71 publications
5
69
2
1
Order By: Relevance
“…2. Different from Fuller et al (2009), who found that attentional allocation is modulated by cue contrast, the modulation effect reported in this paper occurs at the fixation point, which the subject is already attending.…”
Section: Attentional Disengagement or Foecontrasting
confidence: 99%
See 2 more Smart Citations
“…2. Different from Fuller et al (2009), who found that attentional allocation is modulated by cue contrast, the modulation effect reported in this paper occurs at the fixation point, which the subject is already attending.…”
Section: Attentional Disengagement or Foecontrasting
confidence: 99%
“…Furthermore, Fuller et al (2009) found that attention is modulated by cue contrast, concluding that although allocation of attention is automatic and unconscious, the attentional process is gradual rather than all-or-none.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found stronger capture for seen than for unseen cues, despite the two types of cue being physically identical. Attentional capture has recently been demonstrated to operate not as an all-ornone process but rather more gradually, with capture strength increasing with cue contrast (Fuller et al, 2009;Zehetleitner et al, 2013). Another body of work suggests that attentional capture can be modulated through top-down factors such as task set (Ansorge et al, 2011;Folk et al, 1992;Hsieh et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Some studies reported capture by lowcontrast stimuli, even below the threshold for conscious report (McCormick, 1997;Mulckhuyse et al, 2007). Furthermore, brighter stimuli capture attention more strongly than fainter stimuli (Fuller et al, 2009), indicating that capture is not a rigid, all-or-nothing phenomenon, but rather shows gradual scaling properties. Previous studies investigating the relationship between stimulus intensity and capture strength typically used either low or high intensities, rendering any direct comparisons difficult.…”
Section: Introductionmentioning
confidence: 99%